Napping reverses increased pain sensitivity due to sleep restriction. - Brice Faraut; Damien Léger; Terkia Medkour; Alexandre Dubois; Virginie Bayon; Mounir Chennaoui; Serge Perrot (PLoS ONE, 2015)
Study objective To investigate pain sensitivity after sleep restriction and the restorative effect of napping. Design A strictly controlled randomized crossover study with continuous polysomnography monitoring was performed. Setting Laboratory-based study. Participants 11 healthy male volunteers. Interventions Volunteers attended two three-day sessions: "sleep restriction" alone and "sleep restriction and nap". Each session involved a baseline night of normal sleep, a night of sleep deprivation and a night of free recovery sleep. Participants were allowed to sleep only from 02:00 to 04:00 during the sleep deprivation night. During the "sleep restriction and nap" session, volunteers took two 30-minute naps, one in the morning and one in the afternoon. Measurements and results Quantitative sensory testing was performed with heat, cold and pressure, at 10:00 and 16:00, on three areas: the supraspinatus, lower back and thigh. After sleep restriction, quantitative sensory testing revealed differential changes in pain stimuli thresholds, but not in thermal threshold detection: lower back heat pain threshold decreased, pressure pain threshold increased in the supraspinatus area and no change was observed for the thigh. Napping restored responses to heat pain stimuli in the lower back and to pressure stimuli in the supraspinatus area. Conclusions Sleep restriction induces different types of hypersensitivity to pain stimuli in different body areas, consistent with multilevel mechanisms, these changes being reversed by napping. The napping restorative effect on pain thresholds result principally from effects on pain mechanisms, since it was independent of vigilance status.